الأزمة الصومالية وأثرها على أمن البحر الأحمر والمحيط الهندي: القرصنة نموذجا - جيدي، عبدالقادر معلم محمد (مركز بحوث ودراسات دول حوض البحرالأحمر وجامعة البليدة2, 2020)
مر على انهيار الحكومة المركزية في الصومال منذ يناير عام 1991 م ثلاثة عقود، ولا زالت حلقات تلك الأزمة سواء على المستوى المحلي والإقليمي والدولي ماثلة حتى الآن. إذ أن الصومال يحتل موقعا استراتيجيا مهما في منطقة القرن الإفريقي وفي منطقة حوض النيل. فالقرن الإفريقي يعرفه كثير من الباحثين بأنه المنطقة التي يعيش فيها الصوماليون حقيقة، كما أن الصومال يطل على البحر الأحمر بطول أكثر من ألف كيلو متر. ولكل من القرن الإفريقي والبحر الأحمر أهميته الإقليمية والدولية، وهذا ما يجعل للصومال أهمية جيواستراتيجية خاصة، لأنه يمتلك أطول ساحل في إفريقيا، على المحيط الهندي (2200 كلم) والبحر الأحمر (1133 كلم). إن موقع الصومال الاستراتيجي جغرافيا وسياسيا واقتصاديا وأمنيا، جعلها مطمعا للقوى الاستعمارية الأوروبية قديما، ومثار إغراء لجيرانها لأخذ حصتهم منها، فأصبحت النتيجة تقسيم الأراضي الصومالي إلى خمسة أجزاء من أجل نهب ثرواته وخيراته وإعاقة أبنائه عن الاستقرار. ونالت اثنتان من تلك الأجزاء استقلالهما وحققا الوحدة بينهما تحت اسم جمهورية الصومال. والبحر الأحمر له أهمية كبرى من ناحية الأمن القومي بصفة عامة، وأمن البلدان العربية والإفريقية المشاطئة للبحر الأحمر سلما وحربا. تهدف الدراسة إلى تعريف كل من منطقتي القرن الإفريقي والبحر الأحمر مع تناول الأهمية الجيواستراتيجية لهاتين المنطقتين. وتركز الدراسة على قضية القرصنة في المياه الصومالية وأسباب نشأتها وتطورها، وأثرها على الصومال وعلى أمن منطقة البحر الأحمر والمحيط الهندي في ظل المتغيرات والمهددات المحلية والإقليمية والدولية التي تتعرض لها منطقة البحر الأحمر. تأخذ الدراسة المنهج الوصفي التحليلي لوصف وتحليل قضية القرصنة وأسبابها ومآلاتها في المنطقة.
Three decades have passed since the collapse of the central government in Somalia since January 1991, and the episodes of that crisis, whether on the local, regional and international levels, are still present. As Somalia occupies an important strategic position in the Horn of Africa and in the Nile Basin region. The Horn of Africa is known by many researchers as the region in which the Somalis really live, and Somalia overlooks the Red Sea with a length of more than a thousand kilometers. Both the Horn of Africa and the Red Sea have regional and international importance, and this makes Somalia a special geo-strategic importance, as it has the longest coast in Africa, on the Indian Ocean (2,200 km) and the Red Sea (1,133 km). The strategic location of Somalia geographically, politically, economically and security, made it coveted by the European colonial powers in the past, and provoked a temptation for its neighbors to take their share of it, and the result became the division of Somali lands into five parts in order to plunder its wealth and goods and impede its children from stability. Two of those parts gained their independence and achieved unity between them under the name of the Somali Republic. The Red Sea is of great importance in terms of national security in general, and the security of the Arab and African countries bordering the Red Sea is peace and war. The study aims to define each of the Horn of Africa and the Red Sea regions while addressing the geostrategic importance of these two areas. The study focuses on the issue of piracy in Somali waters, the causes of its origin and development, and its impact on Somalia and on the security of the Red Sea and the Indian Ocean in light of the local, regional and international changes and threats to which the Red Sea region is exposed. The study takes the descriptive and analytical approach to describe and analyze the issue of piracy, its causes and consequences in the region.
Keywords: القرصنة البحرية -- البحر الأحمر -- القرن الأفريقي -- الصومال